MENYIAPKAN SULTAN PEREMPUAN: LEGITIMASI LANGIT DAN KEKUATAN REGIM SULTAN HEMENGKUBUWONO X - Bayu Dardias Kurniadi (Masyarakat Indonesia, 2016)
Sultan Hamengkubuwono (HB) X of Yogyakarta has chosen his eldest daughter as his successor in a traditionally patrilineal Sultanate. This paper discusses the controversy surrounding Sultan HB X’s decision by measuring the impact of his proclamations and orders for the Sultanate’s long-term regime effectiveness. I arguethat Sultan HB X’s proclamations and orders based, which were based on mysticism and a sense of divinity, have been ineffectual for maintaining regime effectiveness inside and outside of the Sultanate. Within the Sultanate, the Sultan’s siblings have argued that his decisions contradict the Sultanate’s centuries-long tradition of rules (paugeran). Outside the palace walls, broader society has been divided over Sultan HB X’s choice. One group supports Sultan HB X’s decision, while the other group is determined to hold on firmly to their patriarchal cultural and historical traditions. While Sultan HB X’s proclamations and orders have been ineffectual in maintaining the Sultanate and its influence, his decisions have even brought about an enormous challenge to the survival prospectsof the Sultanate itself.Keywords: political legitimation, regime, Sultan Hamengkubuwono, Yogyakarta Sultanate ABSTRAKPada 2015, Sultan Hamengkubuwono (HB) X mengeluarkan empat kali sabda yang berkaitan dengan suksesi kepemimpinan di Kasultanan Yogyakarta. Tanpa memiliki putra laki-laki, Sultan HB X menunjuk putri sulungnya sebagai penerus tahta yang menganut patrilineal. Tulisan ini membahas tentang efektifitas regim Sultan HB X terutama dilihat dari implikasi yang timbul dari Sabda Raja dan Dawuh Raja. Saya berargumen bahwa penggunaan petunjuk langit sebagai basis legitimasi politik tidak cukup efektif menciptakan dukungan politik. Kondisi ini menjadi ciri melemahnya regim aristokrasi, tidak hanya diluar lingkungan Kasultanan, tetapi justru lebih melemah ke dalam. Legitimasi mistisisme yang berdasarkan petunjuk langit tidak mampu menjadi basis legitimasi ditengah masyarakat yang berubah semakin rasional. Di internal, Sabda dan Dawuh Sultan HB X menghilangkan kemampuan kasultanan untuk memilih pemimpin politik masa depan dan bertentangan dengan ketentuan (paugeran) yang selama ini berlangsung. Di luar tembok istana, masyarakat terbelah antara mendukung Sultan dan tantangan budaya, adat dan sejarah. Kondisi ini merupakan tantangan terbesar Kasultanan Yogyakarta dan demokrasi Indonesia.Kata kunci: legitimasi politik, Sultan Hamengkubuwono, Kasultanan Yogyakarta